2013
DOI: 10.1182/blood-2012-12-473470
|View full text |Cite
|
Sign up to set email alerts
|

Apc regulates the function of hematopoietic stem cells largely through β-catenin–dependent mechanisms

Abstract: • Apc regulates the function of HSCs/HPCs largely through a b-catenin-mediated pathway.• Multiple downstream targets of Apc may be involved in the regulation of HSC self-renewal. . In assays of long-term stem cell function, the HSCs with deficiency of both Apc and b-catenin displayed a significantly enhanced self-renewal capacity compared with b-catenin-deficient and control HSCs. Our findings suggest that Apc regulates the survival, proliferation, and differentiation of HSCs/HPCs largely through a b-catenin-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Of note, inhibition of β‐Cat/TCF with iCRT3 also reduced cell growth in SFM cultures which is consistent with previous studies linking β‐Cat to hematopoietic stem and progenitor cell proliferation (Fig. I) . In summary, the IGF‐1R and β‐Cat/TCF axis appears to mediate the bulk of the growth‐promoting activities of osteoblasts’ paracrine factors on hematopoietic progenitors.…”
Section: Resultssupporting
confidence: 90%
“…Of note, inhibition of β‐Cat/TCF with iCRT3 also reduced cell growth in SFM cultures which is consistent with previous studies linking β‐Cat to hematopoietic stem and progenitor cell proliferation (Fig. I) . In summary, the IGF‐1R and β‐Cat/TCF axis appears to mediate the bulk of the growth‐promoting activities of osteoblasts’ paracrine factors on hematopoietic progenitors.…”
Section: Resultssupporting
confidence: 90%
“…The deletion of Apc or β-catenin was induced by pI-pC injection as we previously described(18). We monitored cohorts of mice for up to 8 months by CBC analysis monthly.…”
Section: Resultsmentioning
confidence: 99%
“…showed that only slightly increased levels of canonical Wnt signaling have a positive effect on HSC repopulation capacity(45). Our recent studies showed that Apc function in hematopoietic stem/progenitor cells is largely dependent on β-catenin(18). Here, we provide additional evidence that reduced doses of β-catenin by heterozygous deletion is sufficient to reverse Apc-heterozygous-induced expansion of HSCs as well as the functional defects of Apc haplo-insufficient HSCs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations